ANALISIS KESIAPAN PENERAPAN BASIS AKRUAL DALAM LAPORAN KEUANGAN (Studi pada Pemerintah Kabupaten Aceh Barat) - Lisma Nazrah, Hasan Basri, Muhammad Arfan. (Jurnal Akuntansi, 2015)
Abstract: The implementation of the accrual basis in the government financial statements has been an issue since the issuance of Government Regulation(PP) No. 71/2010 replacing PP No. 24/2005. The significant differenceis the change of the accounting basis used. The PP 24/2005 used cash basis to the accrual basis of accounting, then the PP 71/2010 the basis of accounting used is PP 24/2005. This study aimed to analyze the readiness of the implementation of the accrual basis in the financial statements at government agencies. The location chosen was the Government of West Aceh District were divided into several dimensions, namely the handling of change management, the level of acceptance and awareness of the needs of the accrual basis. Techniques of data collection is done by distributing questionnaires to all respondents who are the employees who are directly involved as preparers of financial statements. The results showed that the readiness of the implementation of the accrual basis in the financial statements in West Aceh district government are included in the category of adequately ready. Keywords: Readiness implementation of the accrual basis in the financial statements, ManagingChanges,Levelof Acceptance and awareness of the need for Accrual Basis. Abstrak:Penerapan basis akrual dalam laporan keuangan pemerintah telah menjadi isu sejak diterbitkannya PP No. 71/2010 menggantikan PP No. 24/2005. Perbedaan yang signifikan antara lain terdapat pada pengubahan basis akuntansi yang digunakan. Pada PP No.24/2005 digunakan basis akuntansi berbasis kas menuju akrual, maka pada PP No.71/2010 basis akuntansi yang digunakan adalah PP No. 24/2005. Penelitian ini bertujuan untuk menganalisis kesiapan penerapan basis akrual dalam laporan keuangan pada instansi pemerintah. Lokasi yang dipilih adalah Pemerintah Kabupaten Aceh Barat yang dibedakan menjadi beberapa dimensi, yaitu penanganan manajemen perubahan, tingkat penerimaan dan kesadaran akan kebutuhan basis akrual. Tehnik pengumpulan data dilakukan melalui penyebaran kuesioner kepada seluruh responden yang merupakan para pegawai yang terlibat secara langsung sebagai pembuat laporan keuangan.Hasil penelitian menunjukkan bahwa kesiapan penerapan basis akrual dalam laporan keuangan pada Pemerintah Kabupaten Aceh Barat termasuk dalam kategori cukup siap. Kata kunci: Kesiapan penerapan basis akrual dalam laporan keuangan, Penanganan Manajemen Perubahan, Tingkat Penerimaan, dan Kesadaran akan Kebutuhan Basis Akrual.